Conservation gone to the dogs: when canids rule the beach in small coastal reserves - TA Schlacher; Mike Weston; D Lynn; DS Schoeman; CM Huijbers; AD Olds; S Masters; RM Connolly (2015)
On most developed coastlines, dunes backing ocean beaches constitute an urbanised landscape mosaic containing remnant pockets of small conservation areas. Urbanised beaches are also prime sites for domestic dogs, known to be environmentally harmful in many other settings. It is unknown, however, whether small, protected parcels of dune are adequate for biological conservation and whether dogs compromise their functional conservation objectives. Here we examine, for two small (2 km ocean boundary) reserves in Eastern Australia abutting an urban area, whether such small reserves can continue to function as effective conservation instruments on ocean beaches, using scavenger community composition and efficiency to assess ecosystem function. Two non-native species of canids—domestic dogs (Canis lupus familiaris) and red foxes (Vulpes vulpes)—were ubiquitous and numerous inside conservation areas, to the point of having become the most abundant vertebrate scavengers at the beach-dune interface, outcompeting native scavengers for wave-cast carrion. Dogs and foxes have effectively supplanted raptors, normally abundant on non-urban beaches in the region, and other avian scavengers, as the principal consumers of animal carcasses both inside the declared reserves and at the urban beach. Whilst the ecological threats posed by foxes are widely and intensively addressed in Australia in the form of fox-control programs, dog controls are less common and stringent. Our data emphasize, however, that managing domestic dogs may be required to the same extent in order to maintain key forms and functions in coastal reserves situated close to urban areas.